Science Communication and Open Access: The Critique of the Political Economy of Capitalist Academic Publishers as Ideology Critique - Manfred Knoche; Christian Fuchs (tripleC, 2020)
Starting from a theoretical and methodological foundation of an academic ideology critique, the production, distribution and valorisation of science communication will be analysed in exemplary fashion. The focus is on the criticism of publishing houses' business models in the sphere of open Access publishing. These models are propagated and implemented by science and politics. Thus, academic publications continue to be traded as commodities. The existing relationships of power and domination are thereby reproduced. In contrast, the emancipatory potential of non-commercial science communication based on the digitalisation of production and distribution is shown.
Keywords: 330; critique of science; science policy; science communication; Open Access; ideology critique; critique of capitalism; critical communication studies